Evolution of Digital Marketing Strategy in UMKM: Case Study on Business Sustainability - Sudarmanto Saeka; Asraf (Journal of Community Service and Rural Development, 2024)
Digital transformation has changed the business landscape globally, encouraging MSMEs to adopt digital marketing strategies to improve their competitiveness and business sustainability. However, not all MSMEs are able to optimally utilize digital technology due to limited digital literacy, uneven infrastructure, and a lack of skilled human resources in digital marketing. The lack of research discussing the integration of digital marketing and MSME financial management is a knowledge gap that needs to be filled in order to understand how digitalization can effectively improve MSME business sustainability. This study uses a qualitative descriptive method, with data collection through semi-structured interviews with MSME owners, digital marketing practitioners, academics, and e-commerce representatives. The results of the study show that digital marketing strategies based on social media, e-commerce platforms, and financial technology have a significant impact on MSME visibility and profitability, although challenges such as fluctuations in advertising costs and limited digital literacy are still major obstacles. These findings provide theoretical contributions to the development of MSME digital marketing literature and can practically be a guideline for MSME actors in optimizing their digital strategies. Therefore, further research is recommended to explore the effectiveness of government policies and the influence of financial technology sustainability in supporting MSME marketing digitalization.